NUMERICAL ANALYSIS OF Al2O3-WATER NANOFLUIDS THROUGH SQUARE CROSS-SECTION DUCT WITH SINGLE PHASE MODELS - Ozgen, Filiz; Kamaci, Gurcan (Vinca Inst Nuclear Sci, 2022)
In this study, the effect of various concentrations of Al2O3-water nanofluid on heat transfer in duct with a square cross-section, under conditions of continuous heat flux and laminar forced flow, investigated numerically. Reference experimental application parameters are accepted as reference, calculated with single phase homogeneous model (SPHM) and single phase Brownian model (SPBM) models, and the average heat transfer coefficient results of numerical models are compared with each other and reference experimental data. Numerical results obtained with SPHM and SPBM are in comparison to the relevant experimental data. For SPHM and SPBM results, 0.5%, %1.5, %2.5 Al2O3-water nanofluids, the average deviation rate for the average heat transfer coefficient is 3.35% and 2.36%, 5.24%, 3.43%, 7.74%, and 5.3% according to the reference experimental data respectively. 0.5%, %1.5, %2.5, 2.24%, and 3.81%, 5.86% and 7.47%, 9.58% and 11.6%, respectively, the average heat transfer coefficient is increased by using Al2O3-water nanofluid compared to water. It has been observed that, SPBM has closer results than SPHM model according the relevant experimental data.
Keywords: nanofluid; numerical analysis; heat transfer coefficient; SPBM; SPHM